A Review on Photothermal Conversion of Solar Energy with Nanomaterials and Nanostructures: From Fundamentals to Applications. (6th July 2022) - Cheng, Pengfei; Wang, Dong; Schaaf, Peter
Abstract: Solar energy is a green, sustainable, and de facto inexhaustible energy source for mankind. The conversion of solar energy into other forms of energy has attracted extensive research interest due to climate change and the energy crisis. Among all the solar energy conversion technologies, photothermal conversion of solar energy exhibits unique advantages when applied for water purification, desalination, high‐temperature heterogeneous catalysis, anti‐bacterial treatments, and deicing. In this review, the various photothermal conversion mechanisms based on different forms of heat release are summarized and some of the latest examples are presented. In addition, the necessary prerequisites for solar‐driven photothermal materials toward their practical applications are also discussed. Further, the latest advances in photothermal conversion of solar energy are discussed, focusing on different types of photothermal applications. Finally, a summary is given and the challenges and opportunities in the photothermal conversion of solar energy are presented. This review aims to give a comprehensive understanding of emerging solar energy conversion technologies based on the photothermal effect, especially by using nanomaterials and nanostructures. Abstract : This review presents the broad scope of photothermal applications, offers a comprehensive understanding of the photothermal conversion of solar energy with nanomaterials and nanostructures, and provides guidelines for better design and fabrication of photothermal materials.